A king and vassals' tale: Molecular signatures of clonal integration in Posidonia oceanica under chronic light shortage. (24th August 2020) - Ruocco, Miriam; Entrambasaguas, Laura; Dattolo, Emanuela; Milito, Alfonsina; Marín‐Guirao, Lazaro; Procaccini, Gabriele
Abstract: Under unfavourable conditions, clonal plants benefit from physiological integration among ramets, sharing resources and information. Clonal integration can buffer against environmental changes and lets the plant clone work as a 'macro' organism. Molecular signals that regulate this phenomenon are completely unknown in marine plants. Here we present a first comprehensive study providing insights into the metabolic role of different types of ramets (i.e. apical vs. vertical) in the foundation species Posidonia oceanica . Plants were exposed to 80% diminishing irradiance level (LL) in a controlled mesocosm system. Subsequent multiscale variations in whole transcriptome expression, global DNA methylation level, photo‐physiology, morphology and fitness‐related traits, were explored at different exposure times. We tested the hypothesis that vertical shoots (the 'vassals') can provide vital resources to apical shoots (the 'kings') under energy shortage, thus safeguarding the whole clone survival. Whole transcriptome analysis of leaves and shoot‐apical meristems (SAMs) emphasized signatures of molecular integration among ramets, which strongly correlated with higher organization‐level responses. In both shoots types, the exposure to LL resulted in a growth slowdown throughout the experiment, which started from immediate signals in SAMs. In apical shoots, this was linked to an acclimative response, where they were suffering a mild stress condition, while in vertical ones it fell in a more severe stress response. Yet, they suffered from sugar starvation and showed a clear cellular stress response in terms of protein refolding and DNA repair mechanisms. Several epigenetic mechanisms modulated the observed gene‐expression patterns and the cross‐talk between DNA methylation and the cellular energetic status appeared to regulate shoot metabolism under LL. Synthesis . Our results demonstrate a high level of specialization of integrated ramets within seagrass clones and a 'division of labour' under adverse conditions. Vertical shoots appear to do 'most of the job' especially in terms of resource providing, whereas activated functions in apical shoots were restricted to few important processes, according to an 'energy‐saving' strategy. The response of vertical shoots could be seen as a 'sacrificing response' allowing the survival of 'the king' that is key for ensuring propagation and population maintenance, and for the colonization of new environments. Abstract : Our results demonstrate a high level of specialization of integrated ramets within seagrass clones and a 'division of labour' under adverse conditions. Vertical shoots appear to do 'most of the job' especially in terms of resource providing, whereas activated functions in apical shoots were restricted to few important processes, according to an 'energy‐saving' strategy. The response of vertical shoots could be seen as a 'sacrificing response' allowing the survival of 'the king' that is key for ensuring propagation and population maintenance, and for the colonization of new environments.